Evaluation of various fuel alternatives in terms of sustainability for the ship investment decision using single valued neutrosophic numbers with TOPSIS methods. (February 2023) - Mollaoglu, Mahmut; Bucak, Umur; Demirel, Hakan; Balin, Abit
IMO has introduced regulations to improve fuel quality in the sector to reduce emissions from ships carrying the vast majority of world trade. As a result of these regulations, which were planned gradually, carbon-neutral shipping was targeted. In line with this goal, it was seen that ship operating companies tend to various alternatives to increase fuel quality. This study evaluated various fuel alternatives for ship investment decisions by employing the Technique for Order Preference By Similarity to Ideal Solution (TOPSIS) method under the Single Valued Neutrosophic Sets (SVNS) in terms of sustainability aspects. First, criteria that are specific to the ship investment decision under the aspects of sustainability and their weights were determined. Then, these weights were placed in the model to determine the most sustainable ship fuel produced within the scope of the study. Finally, alternatives determined in terms of fuel type, which is one of the items to be decided on ship investment, were listed according to their degree of sustainability. According to the findings, dual fuel and bio-fuel were selected as more sustainable bunker fuels for today. Technically, findings were evaluated, and the pros and cons of the related bunker fuels were revealed. In the light of the findings, evaluations were made on alternatives.